Computational Methods and Experimental Measurements XX. - Carlomagno, G. M. (WIT transactions on engineering sciences., 2021)
Formed of papers presented at the 20th International Conference on Computational Methods and Experimental Measurements, this volume provides a view of the latest work on the interaction between computational methods and experiments.